Implementasi Pancasila Sebagai Ideologi Negara dalam Kehidupan Bermasyarakat - Alia Cinta Kinda (Universitas Negeri Malang, 2023)
Abstract: Pancasila is the ideology of the Indonesian nation which is also a benchmark for the nation's behavior in society. Pancasila was chosen to be the basis of the Indonesian state as an ideology, to become an identity and also as the principle of the unity of the Indonesian nation. The implementation of Pancasila as the basis of the state is indispensable for the Indonesian people, namely to maintain the existence of the Indonesian nation, because Pancasila contains noble values in every precept of the Indonesian nation which is in accordance with the personality of the Indonesian nation. The research method used in this study used literature research data collection with normative research.Keywords: Pancasila, state ideology, indonesian nationAbstrak: Pancasila merupakan ideologi bangsa Indonesia yang sekaligus menjadi tolak ukur, perilaku bangsa dalam bermasyarakat. Pancasila dipilih menjadi dasar negara Indonesia sebagai ideology, menjadi jati diri serta juga sebagai asas persatuan bangsa Indonesia. Implementasi Pancasila sebagai dasar negara sangat diperlukan bagi masyarakat Indonesia yaitu untuk menjaga eksistensi bangsa Indonesia, karena di dalam Pancasila ada nilai-nilai luhur setiap sila-sila bangsa Indonesia yang sesuai dengan kepribadian bangsa Indonesia. Metode penelitian yang dilakukan dalam penelitian ini memakai pengumpulan data literature research dengan penelitian normatif.Kata kunci: Pancasila, ideologi negara, bangsa indonesi